EFFICIENCY OF CREATIVE THINKING ABILITY IN AUGMENTED REALITY-BASED LEARNING MEDIA THE ACID RAIN THEME - Fitria Ramadhani; Sjaifuddin Sjaifuddin; Septi Kurniasih (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2022)
This research was conducted due to the lack of students' awareness of the phenomenon of acid rain. The phenomenon of acid rain can be harmful to health and ecosystems. Whereas acid rain can be prevented by increasing the awareness of students through improving the quality of education, especially the ability to think creatively which is expected to help find solutions to minimize the impact of acid rain. However, students in Indonesia have a low quality of education which causes students' creative thinking skills to be low. This study aims to determine the efficiency of Augmented Reality-based learning media in the development of creative thinking skills of seventh grade students on the theme of Acid Rain. Augmented Reality-based learning media is a technology that combines 2D and 3D virtual objects from interactive applications, thus helping in growing students' creative thinking skills. The research method used is Research and Development (RD) according to Thiagarajan (1974) which was adapted based on the 4-D model. This model consists of 4 stages of development, namely define, design, develop, and disseminate. But the research is limited to the develop stage, because this research only focuses on the efficiency level of the Augmented Reality-based learning media developed. The results of the study based on the efficiency test of learning media based on Augmented Reality with the theme of acid rain for class VII SMP obtained an average value of 88.54% in the very efficient category. Keywords: Learning Media Based on Augmented Reality, Acid Rain, Creative Thinking Ability.